Knowledge Transfer for Institution and Human Resources Empowerment to Develop Ecotourism in Pasir Mendit, Jangkaran Village, Temon District, Kulon Progo Regency - Rahatmawati, Istiana; Prasetya, Johan Danu; Maharani, Ph.D, Yohana Noradika; Happitasyari, Stevanie (Jurnal Mineral, Energi dan Lingkungan, 2024)
The research aims to develop Wana Tirta Pasir Mendit ecotourism, Jangkaran Village, Temon District, Kulon Progo Regency. Knowledge transfer has been used in developing institutions and human resources empowerment. Digital marketing can be used to promote Wana Tirta Pasir Mendit ecotourism through the creation of a website, social media content, and optimization of Google Maps. Therefore, the involvement of local youth in the development of the Wana Tirta Pasir Mendit ecotourism project can contribute to the improvement of human resources capacity and attract tourists through youth empowerment, capacity development, introduction to local culture, and the development of tourism products. To increase the capacity of human resources and draw tourists to Wana Tirta Pasir Mendit ecotourism through digital promotion, local youth involvement in the project's development is crucial. To measure the effectiveness of knowledge transfer in empowering institutions and human resources, several methods had been used, including competency evaluation, and performance assessment. The study found that knowledge transfer is effective in empowering institutions and human resources of Wana Tirta Pasir Mendit ecotourism.